(untitled) (International Journal of Engineering and Computer Science, 2013)
Recent developments in digital image and Internet technology help the common users to easily produce illegal copies of the images. In order to solve the copyright protection problems of the image, several watermarking schemes have been widely used. Very few watermarking schemes have been proposed for defining the copyrights of color image. To resolve the copyright protection problem of color image, we propose an effective, robust and imperceptible color image watermarking scheme. This scheme embeds the watermark into cover image in (Red, Green, Blue) RGB space. The combinations of Discrete Wavelet Transform (DWT) and Singular Value Decomposition (SVD) are used to embed the watermark. In the combination of Discrete Wavelet Transform (DWT) and Singular Value Decomposition (SVD), the singular values of different sub band coefficients are modified using different scaling factors to embed the singular values of the watermark. The copy of the watermark is embedded into four sub band coefficients which is very difficult to remove or destroy. The combination of DWT and SVD increases the security, robustness and imperceptibility of the scheme. In this project, we employ watermarking for video also